Radiografia dos espumantes brasileiros - Cavagnolli, Natália Inês (My University, 2022)
Considered the exponent product of the wine sector in Brazil, the Brazilian sparkling wine has been standing out worldwide due to its quality, with awards in the main competitions in the area, also reflecting in the increment of the consumption of the drink, with an increase of 262% from 2005 to 2015. The sales in 2019 were 30.74 million liters, 2.36% higher than in 2018. The revenue of sparkling wine sales followed this growth, with muscatel reaching the mark of R$ 485 million and natural sparkling wines the mark of R$ 861 million only in 2019. Listed as the main national product, there is a need for more meticulous production and quality control, which has been happening over the years through investments and adaptations to quality management systems, in addition to the use of new technologies for the preparation of sparkling wines. The samples analyzed in this study are from 89 wineries from different regions of Brazil, which participated in the XI Brazilian Sparkling Wine Contest, in 2019, held in the city of Garibaldi, Rio Grande do Sul. The 243 registered samples were sent to the Laboratory Lavin, in the city of Flores da Cunha, to carry out the analysis of total titratable acidity (g/L of tartaric acid), volatile acidity (g/L of acetic acid), total reducing sugars (g/L of glucose), alcoholic strength (% v/v), pH, pressure in bottle (atm at 20ºC) and total sulfur dioxide (mg/L), according to the methodologies of the Ministry of Agriculture, Livestock and Supply (MAPA), the World Organization of Vine and Wine (OIV) and Barceló (1990), being subsequently forwarded to statistical analysis. The pH results ranged between 3.16 and 3.33 for all categories, while the analysis of total titratable acidity, volatile acidity, alcoholic strength and total sulfur dioxide showed excellence results. The parameters with higher variation in the results were pressure in bottle and total reducing sugars, showing the need for greater control in the elaboration and filling, mainly in the handling of the expedition liquor. [resumo fornecido pelo autor]
Considerado o produto expoente do setor vitivinícola do Brasil, o espumante brasileiro vem se destacando cada vez mais no cenário mundial devido à qualidade, com premiações nos principais concursos da área, o que refletiu também no aumento do consumo da bebida, com um acréscimo de 262% de 2005 a 2015. Em 2019 foram comercializados 30,74 milhões de litros, 2,36% a mais que em 2018. Acompanham esse crescimento os valores oriundos das vendas de espumantes, com o Moscatel atingindo a marca de R$ 485 milhões e os espumantes naturais a marca de R$ 861 milhões somente no ano de 2019. Elencado como o principal produto nacional, evidencia-se a necessidade de uma produção e controle de qualidade cada vez mais minuciosos, o que vem acontecendo com o passar dos anos através de investimentos e adaptações aos sistemas de gestão de qualidade, além do uso de novas tecnologias durante a elaboração dos espumantes. As amostras analisadas neste estudo têm como origem 89 vinícolas de diferentes regiões de todo o Brasil e foram provenientes do XI Concurso Espumante Brasileiro, em 2019, realizado no município de Garibaldi, Rio Grande do Sul. As 243 amostras inscritas foram encaminhadas ao Laboratório Lavin, no município de Flores da Cunha, para realizar as análises de acidez total titulável (g/L de ácido tartárico), acidez volátil (g/L de ácido acético), açúcares redutores totais (g/L de glicose), graduação alcoólica (% v/v), pH, pressão em garrafa (atm a 20ºC) e dióxido de enxofre total (mg/L), conforme metodologias do Ministério da Agricultura, Pecuária e Abastecimento (MAPA), da Organização Mundial da Vinha e do Vinho (OIV) e Barceló (1990), posteriormente sendo encaminhadas às análises estatísticas. Os resultados de pH permaneceram entre 3,16 e 3,33, para todas as categorias, ao mesmo tempo que as análises de acidez total titulável, acidez volátil, graduação alcoólica e dióxido de enxofre total apresentaram resultados de excelência. Os parâmetros com maior alteração nos resultados foram pressão em garrafa e açúcares redutores totais, mostrando a necessidade de maior controle na elaboração e envase, principalmente no manuseio do licor de expedição. [resumo fornecido pelo autor]
Keywords: Vinhos espumantes; Físico-química; Vinho e vinificação; Sparkling wines; Chemistry, Physical and theoretical; Wine and wine making